Improvement of self efficacy through bibliotherapy in diabetes patient - Isworo, Atyanti (International Journal of Research in Medical Sciences, 2018)
Background: Diabetes Mellitus is also known diabetes, as a chronic disease which will trigger various complications both microvascular and macrovascular. This is what leads diabetes patient to have high risk of low self-efficacy. Low of self-efficacy causes a decrease in self care. Therefore, to improve the patient’s self-efficacy is changing their mindset. Bibliotherapy is a treatment using written materials to guide and encourage the patients to challenge unhelpful thoughts. This research aims at discovering the influence of bibliotherapy on self-efficacy of diabetes patients. Methods: This is a quantitative research using quasi-experimental with control group design. The number of samples in this research is 40 respondents, consisting of 20 intervention groups and 20 control group by simple random sampling method. The sample in this research is diabetes patients with such inclusion criteria as (1) 36-60 years of age, (2) having the ability to read well, (3) willing to be a research respondent. Meanwhile, the exclusion criteria are (1) diabetes patient with weak condition, (2) experiencing loss of consciousness, (3) having visual and audio problems, and (4) diabetes patient with mental disability. The intervention group undergoes bibliotherapy for 8 session, each session for 60 minutes. The Diabetes Management Self Efficacy Scale (DMSES) to determine the total score of self-efficacy. Results: Most respondents are middle-aged adults (36-55 years) in both groups. Most respondents have suffered from diabetes for less than 5 years, unemployed and tend to have normal BMIs and also obese category 1. The mean score post test in intervention and control group is 37.00 and 25.65 respectively. The results show that there are differences in self-efficacy scores after treatment in control and intervention groups (p=0.000). Conclusions: From our study we concluded that bibliotherapy could improve self-efficacy in diabetic patients.